Unconventional Monetary Policies: Lessons from the Past and the Present to Future Monetary Policy Frameworks - Duarte, Cristiano Boaventura; Modenesi, André; Licha, Antonio; Carré, Emmanuel (Brazilian Keynesian Review, 2020)
This article intends to debate important aspects related to past and recent experiences of monetary policy accommodation, focusing on unconventional monetary policies. We intend to draw lessons from these experiences to discuss the design of future monetary policy frameworks.First, by reporting several historical experiences of major central banks, we highlight that policies which after 2008 crisis were considered “unconventional” were not new, with central banks intervening to avoid broader deterioration of macro-financial conditions.Moreover, analyzing the experience of the European Central Bank after 2008, we observe this institution has adapted its measures according to its former programs and to other central banks' experiences, to face numerous challenges and enhance its framework. Finally, we argue that central banks need to take advantage of past and recent experiences to improve the design of their future monetary policy frameworks under an evolutionary perspective. Based on this, measures previously implemented would have three possible destinations in new frameworks: i) Be discarded, due to their predominantly adverse effects; ii) Not be regularly implemented, but be kept as backstop mechanisms if needed; iii) Be incorporated as regular measures of monetary policy frameworks.